2020
DOI: 10.1093/schbul/sbaa104
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Auditory Processing and Underlying Structural Changes in 22q11.2 Deletion Syndrome

Abstract: The 22q11.2 deletion syndrome (22q11.2 DS), one of the highest genetic risk for the development of schizophrenia, offers a unique opportunity to understand neurobiological and functional changes preceding the onset of the psychotic illness. Reduced auditory mismatch negativity response (MMN) has been proposed as a promising index of abnormal sensory processing and brain pathology in schizophrenia. However, the link between the MMN response and its underlying cerebral mechanisms in 22q11.2 DS remains unexamined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…In addition, there are reductions of the MD connectivity in patients with schizophrenia ( Parnaudeau et al, 2013 ). Similarly, a couple of studies found reductions in the volume of the MGN in 22q11.2 deletion syndrome patients, a genetic disorder, which confers high risk for schizophrenia and frequently courses with AH ( Cantonas et al, 2021 , Mancini et al, 2020 ).…”
Section: Introductionmentioning
confidence: 96%
“…In addition, there are reductions of the MD connectivity in patients with schizophrenia ( Parnaudeau et al, 2013 ). Similarly, a couple of studies found reductions in the volume of the MGN in 22q11.2 deletion syndrome patients, a genetic disorder, which confers high risk for schizophrenia and frequently courses with AH ( Cantonas et al, 2021 , Mancini et al, 2020 ).…”
Section: Introductionmentioning
confidence: 96%
“…The impedance was kept below 30 kΩ for all electrodes and below 10 kΩ for the reference and ground electrodes. The preprocessing steps were performed by using the free academic software Cartool (31)(https://sites.google.com/site/cartoolcommunity/home) as previously described (24,30,32,33). In detail, the number of electrodes was reduced from 256 to 204 by eliminating the noisy electrode signals from the cheeks and neck.…”
Section: Methodsmentioning
confidence: 99%
“…The pre-processing steps, including band-pass filtering , exclusion of artefactual periods, interpolation of noisy channels, and re-referencing were performed by using the free academic software Cartool (45,51). For further details: Supplementary Materials.…”
Section: Eeg Data Acquisition During Visual Paradigm and Pre-processingmentioning
confidence: 99%